2019
DOI: 10.1128/jvi.00707-19
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Lymphotoxin-α, a Herpesvirus Entry Mediator (HVEM) Ligand, Affects Herpes Simplex Virus 1 InfectionIn VivoDifferently than the Absence of Other HVEM Cellular Ligands

Abstract: Previously, we reported that the absence of herpesvirus entry mediator (HVEM) decreases latency but not primary infection in ocularly infected mice. Recently, we reported that similar to the absence of HVEM, the absence of HVEM ligands (i.e., LIGHT, CD160, and B and T lymphocyte attenuator [BTLA]) also decreased latency but not primary infection. Similar to LIGHT, CD160, and BTLA, another member of tumor necrosis factor (TNF) superfamily, lymphotoxin-␣ (LT␣), also interacts with HVEM. To determine whether LT␣ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
(104 reference statements)
1
9
0
Order By: Relevance
“…We also demonstrated that efficient levels of latency, but not reactivation, depended on BTLA, CD160, and LIGHT (40). On the other hand, expression of LT␣ did not affect latency levels (41). To determine whether rescue of latency and reactivation in HVEM hWT , HVEM hY23A , or HVEM mY23A transgenic mice is due to differential effects on known HVEM binding partners in HVEM Ϫ/Ϫ and transgenic mice, expression of BTLA, CD160, and LIGHT was measured in the TG of mice latently infected with HSV-1 by qRT-PCR as described above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that efficient levels of latency, but not reactivation, depended on BTLA, CD160, and LIGHT (40). On the other hand, expression of LT␣ did not affect latency levels (41). To determine whether rescue of latency and reactivation in HVEM hWT , HVEM hY23A , or HVEM mY23A transgenic mice is due to differential effects on known HVEM binding partners in HVEM Ϫ/Ϫ and transgenic mice, expression of BTLA, CD160, and LIGHT was measured in the TG of mice latently infected with HSV-1 by qRT-PCR as described above.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we have also demonstrated that BTLA, LIGHT, and CD160 play roles in efficient establishment of latency but not in reactivation (40). LT␣, on the other hand, does not affect the establishment of latency (41). Currently, the mechanism of HVEM function in the latency and reactivation cycle is unclear.…”
mentioning
confidence: 79%
“…Each swab was placed in 1 ml of tissue culture medium and stored at -80°C until processing. The amount of virus in the medium was determined by a standard plaque assay using RS cells as we described previously (41,73).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time RT-PCR (qRT-PCR) was performed using QuantStudio 5 System (Applied Biosystems, Foster City, CA, USA) in 384-well plates as we described previously. 118,119…”
Section: Rna Extraction Cdna Synthesis and Taqman Rt-pcrmentioning
confidence: 99%